Without reservations (1946) [videorecording (DVD)] - LeRoy, Mervyn, 1900-1987; Colbert, Claudette; Wayne, John, 1907-1979; Defore, Don, 1913-1993 (John Wayne collection (Warner Bros.), 2007)
An author is looking for a man to play the leading role in the film version of her book when she meets returning World War II soldiers on a train, and she is determined to turn one of them into the needed actor.